The Anatomy of Ethical Leadership: To Lead Our Organizations in a Conscientious and Authentic Manner - Lyse Langlois (Athabasca University Press, 2011)
Performance at all costs, productivity without regard to consequences, and a competitive work environment: these are the ethical factors discussed in The Anatomy of Ethical Leadership, which highlights issues in workplace culture while looking into a brighter future for labour ethics. Langlois maintains that an enhanced awareness of the process of ethical decision making in difficult situations will lead to the establishment of practices that encourage productive relationships between co-workers. Will the twenty-first century be marked as an era leading to a healthier work environment? The Anatomy of Ethical Leadership aims to serve those in human resource management and those concerned with practical work ethic.